RFID handbook : fundamentals and applications in contactless smart cards, radio frequency identification and near-field communication - Finkenzeller, Klaus (John Wiley and Sons, 2010)
This is the third revised edition of the established and trusted RFID Handbook ; the most comprehensive introduction to radio frequency identification (RFID) available. This essential new edition contains information on electronic product code (EPC) and the EPC global network, and explains near-field communication (NFC) in depth. It includes revisions on chapters devoted to the physical principles of RFID systems and microprocessors, and supplies up-to-date details on relevant standards and regulations. Taking into account critical modern concerns, this handbook provides the latest information.- Resumé vydavatel
Keywords: RFID technologie; automatická identifikace; čipové karty; RFID technology; automatic identification; smart cards; elektronické knihy; příručky; electronic books; handbooks and manuals